Justice Dilemma: Prison for Child Offenders or Recovery for Victims of Sexual Violence in Jepara? - Didik Purnomo (Faculty of Law, Universitas Negeri Semarang, 2025)
This research explores the dilemma of law enforcement in cases of sexual violence against children in Jepara. The study analyzes two conflicting perspectives: the imposition of prison sentences on child offenders and efforts for the recovery of victims. A normative research method is used through the analysis of regulations, particularly related to the Child Criminal Justice System Law, and the analysis of court decisions from the Jepara district court from 2019 to 2024. The results indicate the complexity in the application of law that considers aspects of juvenile punishment and victim protection. On one hand, there is a demand for justice from victims who want severe punishment for the perpetrators. On the other hand, there are concerns about the negative impact of detention on the perpetrator's child, who may need rehabilitation and guidance more. Research highlights the importance of a holistic and integrated approach in handling cases of sexual violence against children, which considers the interests of victims and restorative justice efforts for child perpetrators. This research provides policy recommendations that favor the recovery of victims and the rehabilitation of child perpetrators, as well as emphasizing the importance of synergy among related institutions in addressing cases of sexual violence against children in Jepara